Modeling the process of searching for operationally significant information from open state information resources - E. Yu. Nikulina; L. A. Obukhova; E. A. Rogozin (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The purpose of the study is to increase the effectiveness of measures to identify, investigate and disclose offenses and crimes based on the analysis of Internet resources in order to identify and structure information suitable for intellectual analysis; identify relationships between data categories, develop a model for obtaining operationally significant information from open government information resources. Method. The study is based on the use of statistical analysis to describe the general structure of information about an individual posted in official state information resources. A categorized list of relevant web resources containing operationally significant information about a person or subject of a crime is compiled on the basis of expert assessments of law enforcement officers. To determine the relationships between data categories, a graphical-analytical method for studying information flows was used, and a graph model for obtaining operationally significant information from open state information resources was built. Result. The results of the analysis of Internet resources in order to identify information suitable for intellectual analysis are presented, their structuring is carried out, relationships between data categories are identified, and a model for obtaining operationally significant information from open state information resources is developed. Conclusion. The conducted system analysis of the state information resources of the Internet made it possible to identify the relationship between the categories of data and use them to obtain operationally significant information from open state information resources. In practice, the constructed model can be used to optimize fuzzy search. To solve this problem, it seems possible to use Kohonen neural networks or Hamming algorithms. The apparatus of neural networks will allow you to determine patterns and optimize the search for operationally significant information.